2020
DOI: 10.7150/jca.49262
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic evolution-related Gene Analysis based on both single-cell and bulk transcriptomics in Colorectal Cancer

Abstract: Purpose: The patients diagnosed with colorectal cancer (CRC) are likely to undergo differential outcomes in clinical survival owing to different pathologic stages. However, signatures in association with pathologic evolution and CRC prognosis are not clearly defined. This study aimed to identify pathologic evolution-related genes in CRC based on both single-cell and bulk transcriptomics. Patients and methods: The CRC single-cell transcriptomic dataset (GSE81861, n=590) with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…[ 45 , 46 ] HOXC6 encodes a highly conserved transcription factor, and multivariate analysis showed that increased HOXC6 expression was an independent risk factor for poor prognosis in CRC patients [ 47 ]. HOXC6 is considered as a marker gene in the pathological evolution of CRC and can be used to predict the prognosis of CRC patients [ 48 ]. Our results also showed that COAD patients with high HOXC6 expression had a lower survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…[ 45 , 46 ] HOXC6 encodes a highly conserved transcription factor, and multivariate analysis showed that increased HOXC6 expression was an independent risk factor for poor prognosis in CRC patients [ 47 ]. HOXC6 is considered as a marker gene in the pathological evolution of CRC and can be used to predict the prognosis of CRC patients [ 48 ]. Our results also showed that COAD patients with high HOXC6 expression had a lower survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…44 Li et al reported BMP5 was a biomarker in the pathologic evolution process, which was able to be used in the prediction of pathologic stages and prognosis. 45 Nevertheless, the detailed regulatory mechanism of BMP5 remains elusive. BMP5 is an important member of the TGF-β superfamily, which could involve in a series of regulation of cell phenotypes by BMP/SMAD signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al . reported BMP5 was a biomarker in the pathologic evolution process, which was able to be used in the prediction of pathologic stages and prognosis 45 . Nevertheless, the detailed regulatory mechanism of BMP5 remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, HOXC6 was found to be excessively expressed in colorectal cancer tissues; that study also indicated that higher HOXC6 expression was associated with poorer overall survival [ 26 ]. HOXC6 has been included in several prognostic risk models as a signature gene [ 27 ]. Qi et al [ 28 ] utilized public RNA and mRNA sequencing data from The Cancer Genome Atlas database to analyze the expression of HOXC6 in colorectal cancer in relation to the tumor immune microenvironment (TIME).…”
Section: Discussionmentioning
confidence: 99%